2011
DOI: 10.1007/s00421-011-1890-7
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in the salivary melatonin responses to exercise: relation to exercise-mediated tachycardia

Abstract: Salivary melatonin concentration is an established marker of human circadian rhythmicity. It is thought that melatonin is relatively robust to the masking effects of exercise. Nevertheless, the extent and even the direction of exercise-related change is unclear, possibly due to between-study differences in the time of day exercise is completed. Therefore, we aimed to compare melatonin responses between morning and afternoon exercise, and explore the relationships between exercise-related changes in melatonin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
2
14
0
1
Order By: Relevance
“…These observations are related to situations when physical exercise precedes the phase of MLT increase. However, when MLT level is high during training, a further increase is observed [83]. Buxton et al reported a significant increase in MLT among some of the subjects who performed physical exercise in the evening [80].…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are related to situations when physical exercise precedes the phase of MLT increase. However, when MLT level is high during training, a further increase is observed [83]. Buxton et al reported a significant increase in MLT among some of the subjects who performed physical exercise in the evening [80].…”
Section: Physical Activitymentioning
confidence: 99%
“…Marrin et al investigated salivary MLT level and found an elevation in MLT levels after physical exercise in their subjects. These changes also depended on the time of the day when the training was performed [83].…”
Section: Physical Activitymentioning
confidence: 99%
“…Thus, intravenous administration of melatonin in the baboon increases the cardiac output and left ventricular ejection fraction, which implies a positive inotropic action on the heart by melatonin that could increase cardiac output [60]. Measurements of salivary melatonin concentration during and after exercise show that the gradient of the heart rate–melatonin relationship is steeper in the morning than in the afternoon [44]. Taking into account that the absolute increase in melatonin was greater in the morning when the circulating levels of the indoleamine are higher, these results raise the possibility that circulating melatonin favors the increase in cardiac output during exercise and that the time of day alters the relationships between exercise‐mediated sympathetic neural activity and melatonin secretion.…”
Section: Melatonin and Physical Performancementioning
confidence: 99%
“…A later study [32] also failed to show an acute increase in melatonin secretion following morning and afternoon exercise. Although the mechanism underpinning the possible acute alteration in melatonin concentration following exercise remained unknown, a recent report confirmed that the absolute rise in melatonin levels following exercise was greatest and more pronounced in the morning than in the afternoon [44].…”
Section: Influence Of Physical Exercise On Melatonin Levelsmentioning
confidence: 99%
“…Well-trained individuals show an adaptive response to each training that they take part as their oxidative stress regulates and diurnal melatonin levels temporarily increase [16,21]. Total mechanisms of the melatonin alteration following exercises remained unknown, but exercise-induced absolute rise in melatonin levels is more pronounced in the morning compared to the evening [22].…”
Section: Muscle Development Is Under the Effects Of Program Variablesmentioning
confidence: 99%